Efeitos de drogas supressoras de perda óssea no reparo ósseo de ratas normais e ovariectomizadas. Estudo com Alendronato de Sódio e Ranelato de Estrôncio - Grion, Dalva Pazzini (2014)
Postmenopausal osteoporosis due to estrogen deficiency occurs as a consequence of increased bone resorption. Sodium Alendronate (ALD) is a bisphosphonate widely used in the prevention and treatment of osteoporosis that increases bone mineral density and consequently reduces the incidence of fractures. In treatments with high doses or long-term can cause osteonecrosis and atypical fractures. The Strontium ranelate (RE) promotes new bone formation and also inhibits bone resorption by decreasing osteoclast differentiation. As the bone metabolism in normal subjects is different from that in osteoporotic individuals, the aim of this work is to evaluate and compare the effect of suppressing drugs on bone resorption in subjects with normal and estrogen depletion in bone repair. The total of 108 rats was randomly divided into 6 groups of 18 each and underwent surgical ovariectomy (OVX) or sham surgery (SHAM), distributed as follows: OVX / ALD, OVX / OVX and RE / NaCl, SHAM OVX / ALD OVX SHAM / SHAM and OVX RE / NaCl. After ovariectomy (60 days), all animals were treated with the drug relative to the group until the end of the experimental period. After 30 days of treatment, a defect of 5 mm diameter was surgically created in the calvaria of animals. After 7, 15, 45 days, the animals were euthanized and bone pieces removed. The analyses of results was performed by microscopy. The histomorphometry at 15 days shows that the treated groups (ALD and RE) showed greater bone formation compared to untreated (NaCl) in both groups, SHAM and OVX (p <0,05 ANOVA, Tukey). Furthermore, animals treated with RE show increased bone formation compared to the ALD group. Similarly, at 45 days the results indicate that in the edge region of defect, the treated groups (ALD and RE) showed greater bone formation compared to the untreated group (NaCl) in both the SHAM group and the OVX group (p <0,05 ANOVA, Tukey)